The foundations of applying the art of Ikebana in the art works lessons in the Art Education Department - SuhadJawadFaraj Al-Sakani ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
The current research aims to identify the foundations of applying the art of ikebana and how to integrate its applications into lessons on art works in the Department of Art Education at the College of Basic Education. Therefore, the theoretical aspects that enhance the crystallization of the problem of the current research were studied by identifying the beginning of the art of ikebana, its requirements, the foundations of its general principles, and its relationship to handicrafts. In the field of art education, the current research community included all educational lessons on the art of Ikebana published electronically on the Internet, and after seeking the opinions of a group of experts and specialists, a percentage of (10%) of this community was adopted as a sample of (13) typical lessons for the art of Ikebana. Then the researcher designed a tool to analyze the content of these electronic lessons in order to reach the foundations for integrating practical applications of the art of Ikebana into handicraft lessons. After verifying the validity and reliability of the tool, it was applied to the selected samples. The researcher concluded that applying the Japanese art of Ikebana can lead to innovation. There has been a great momentum of new designs in the field of flower arranging by employing the aesthetics of the arts of neighboring peoples in designing and making flowers in the Japanese style. It also recommended the necessity of periodically updating the vocabulary of handicrafts subjects in the departments of art education and suggested conducting studies and research similar to the current study, in a way that serves the educational content of the field. Art education.